A Therapeutic Educational Program in Oral Health for Persons with Schizophrenia: A Qualitative Feasibility Study - Audrey Peteuil; Corinne Rat; Sahar Moussa-Badran; Maud Carpentier; Jean-François Pelletier; Frederic Denis (International Journal of Dentistry)
Objective. The aim of this study was to test the feasibility of a therapeutic educational program in oral health (TEPOH) for persons with schizophrenia (PWS). Design. In a qualitative study, we explored the representation of oral health before and after a TEPOH. Clinical Setting: PWS are at greater risk of decayed and missing teeth and periodontal diseases. In a previous publication, we described the different steps in building a TEPOH by taking into account the experiences of PWS concerning oral health quality of life. This TEPOH aimed at promoting a global health approach. Participants: Voluntary PWS and their caregivers were recruited during face-to-face interviews at “Les Boisseaux” (a psychiatric outpatient centre) in Auxerre (France) and were included in the study between November and December 2016. Intervention: We explored the experiences of participants and their perceptions of oral health before and after the TEPOH with focus group meetings. Results. Four females and three males participated in the study, and the mean age was 29.4 ± 5. Before the TEPOH, the PWS produced 28 ideas about oral health perception and 37 after the TEPOH. After the TEPOH, elements relating to the determinants of oral health (smoking and poor diet) emerged. Conclusions. These results show an evolution in oral health representation, and after some adjustments to the TEPOH, the second step will be to test this program in a large sample to generate a high level of evidence of the impact of TEPOH in the long term.